Simply the best : [compact disc] Classical passion. - Borodina, Olʹga; Domingo, Plácido, 1941-; Legrand, Michel, 1932-2019-; Cura, José, 1962-; Janowski, Marek; Davis, Andrew, 1944-; Luganskiĭ, Nikolaĭ, 1972-; Dohnányi, Christoph von; Leonskaja, Elisabeth; Wolff, Hugh, 1953- (Warner Classics, 2003)
Many of classical music's universally loved treasures come together in a collection that draws upon romantic themes. Included are excerpts from such romantic works as Tristan and Isold; The Firebird ballet; and Tchaikovsky's Piano Concerto no. 1.